(untitled) (ASEAN Engineering Journal, 2014)
Case study area, Wetkaik village (16° 54' N, 93° 27' E) is identified for economic feasibility in this paper. HOMER optimization model plan imputed from total daily load demand, 1167kWhr/day for current energy consuming of 850householdsandaverage wind speed, 3.7 m/s according to NASA data, 10m above the ground in this area is designed. This proposed system is storage wind-diesel hybrid system based on the cost and fuel availability, and resulting power quality for not only to optimize the energy cost but also to decrease the air pollution with effects the environment. Simulation results can be performed with HOMER micropower optimization tool. Special focus is put on sizing the optimal system which gives the lowest levelized cost of energy approximately 0.257 /kWhr according to the village level priority. This project intends to access to a reliable supply of energy as wind-diesel hybrid system application that it is possible to supply of electricity to such remote locations where there is a wind energy source.